A Super High Gain L-Slotted Microstrip Patch Antenna For 5G Mobile Systems Operating at 26 and 28 GHz - Nahas, M. (Engineering, Technology & Applied Science Research, 2022)
Microstrip patch antennas have been widely investigated and used in modern mobile communication technologies including 5G. Previous works in the area demonstrated that such antennas can be designed to operate in the low, mid, and high bands of 5G networks. This paper focuses on high-band millimeter-wave 5G mobile applications. In particular, the proposed microstrip patch antenna was designed to operate at 26 and 28GHz, which are the first introduced and widely used frequency bands of the 5G. This study aims to enhance the gain and other radiation characteristics of the antenna by adding a combination of different slot shapes to a single rectangular patch that is commonly used in other 5G antennas. The results show that an extremely high gain is achieved by inserting two symmetric L-slots and a middle-placed square slot. The dimensions of the slots were simulated and optimized using the CST Studio Suite simulator. A comparative study was also conducted showing that the proposed antenna features higher gain and directivity and provides very good VSWR and efficiency along with a reasonably large enough bandwidth at the two resonance frequencies considered.